Photothermal‐Triggered Sulfur Oxide Gas Therapy Augments Type I Photodynamic Therapy for Potentiating Cancer Stem Cell Ablation and Inhibiting Radioresistant Tumor Recurrence - Tianfu Zhang; You Pan; Meng Suo; Meng Lyu; Jacky Wing Yip Lam; Zhaokui Jin; Shipeng Ning; Ben Zhong Tang (Advanced Science, 2023)
Abstract Despite advances in cancer therapy, the existence of self‐renewing cancer stem cells (CSC) can lead to tumor recurrence and radiation resistance, resulting in treatment failure and high mortality in patients. To address this issue, a near‐infrared (NIR) laser‐induced synergistic therapeutic platform has been developed by incorporating aggregation‐induced emission (AIE)‐active phototheranostic agents and sulfur dioxide (SO2) prodrug into a biocompatible hydrogel, namely TBH, to suppress malignant CSC growth. Outstanding hydroxyl radical (·OH) generation and photothermal effect of the AIE phototheranostic agent actualizes Type I photodynamic therapy (PDT) and photothermal therapy through 660 nm NIR laser irradiation. Meanwhile, a large amount of SO2 is released from the SO2 prodrug in thermo‐sensitive TBH gel, which depletes upregulated glutathione in CSC and consequentially promotes ·OH generation for PDT enhancement. Thus, the resulting TBH hydrogel can diminish CSC under 660 nm laser irradiation and finally restrain tumor recurrence after radiotherapy (RT). In comparison, the tumor in the mice that were only treated with RT relapsed rapidly. These findings reveal a double‐boosting ·OH generation protocol, and the synergistic combination of AIE‐mediated PDT and gas therapy provides a novel strategy for inhibiting CSC growth and cancer recurrence after RT, which presents great potential for clinical treatment.